Analysis of the Types of Prophet's Educational Media from the Perspective of Modern Education Theory - Maisaroh Ritonga; Nursalimah Nursalimah; Ruwaidah Ruwaidah; Betti Megawati; Samsir Samsir (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study examines the educational media used by the Prophet Muhammad within the framework of modern educational theory and its relevance for contemporary learning practices. This research aims to identify the types of media applied by the Prophet, analyze their alignment with current instructional concepts, and highlight their potential contribution to the development of education grounded in Islamic values. This research employs a library-based qualitative approach, with data validity ensured through credibility and dependability techniques, and content analysis used to interpret the collected data. The findings reveal that the Prophet Muhammad utilized a range of instructional media, including human-based media (gestures, physical demonstration, and role modeling), visual media (natural phenomena such as the sun, moon, trees, and rainfall), and audio media. These forms of media, although simple, effectively supported learning and reflect pedagogical principles remarkably consistent with modern instructional frameworks. The study concludes that the Prophet’s pedagogical practices offer a foundational model that predates modern theory and provides valuable insights for enhancing contemporary instructional media design. The novelty of this research lies in its systematic comparison between prophetic media practices and current educational theory, demonstrating their continued relevance. Practically, the study encourages educators and institutions to adopt multimodal, contextual, and learner-centered media approaches inspired by prophetic teaching strategies to improve instructional effectiveness today.